G251(P) Cardiac murmurs in neonates: review of current local practice and clinical outcomes. (12th March 2018) - Rao, H; Shenvi, A
Abstract : Aim: To review the result of modifications to regional network guidelines in the management of neonatal heart murmurs. Background: The local trust guidelines for the management of neonatal heart murmurs were formulated by the modification of the South West Midlands Maternity and Newborn Network (SWMMNN) guidelines. The modifications included the following – Babies with murmurs are reviewed again as inpatients at ≥24 hours of age to identify any change, electrocardiography is not done as first line investigation, outpatient review is done within 2 to 3 weeks as opposed to 2 to 6 weeks and referred to neonatal cardiology outpatient clinic if the murmur is persistent. Methods: This was a retrospective review of 3131 babies born between December 2016 and May 2017. Data was obtained from the case notes and electronic records.Babies with antenatally detected congenital heart disease and babies admitted to the neonatal unit for other reasons were excluded. Results: 93 babies (3%) had murmurs detected at birth. Murmurs resolved in 60 babies (64.5%) within 24 hours. Murmurs persisted for more than 24 hours in 33 babies and all these babies were reviewed in neonatal outpatient clinic in 2–3 weeks. The mean waiting time for echocardiography was 15 weeks. 25 babies were discharged (75%) from the clinic after resolution of the murmur. Out of the remaining 8 babies, one baby' s murmur disappeared, one had an innocent murmur, two had congenital heart disease diagnosed (severe pulmonary stenosis with right ventricular hypertrophy and dilatation, moderate pulmonary stenosis) and were transferred to a tertiary centre. Four are awaiting outpatient appointments. Providing written information to general practitioners and parents was found to be inadequate. Conclusion: Review at ≥24 hours of age significantly reduces the need for investigations, outpatient appointments and also decreases parental anxiety. Communication to GPs and parents should be improved with emphasis on when and whom to seek help. A generic letter to GPs and a parent information leaflet were formulated to improve this. There is a need for reduction in the mean waiting time for outpatient echocardiography. This could be achieved by training more paediatricians to develop an expertise in cardiology.